Pharmacodynamics of long-acting folic acid-receptor targeted ritonavir-boosted atazanavir nanoformulations. (February 2015) - Puligujja, Pavan; Balkundi, Shantanu S.; Kendrick, Lindsey M.; Baldridge, Hannah M.; Hilaire, James R.; Bade, Aditya N.; Dash, Prasanta K.; Zhang, Gang; Poluektova, Larisa Y.; Gorantla, Santhi; Liu, Xin-Ming; Ying, Tianlei; et al.
Abstract: Long-acting nanoformulated antiretroviral therapy (nanoART) that targets monocyte-macrophages could improve the drug's half-life and protein-binding capacities while facilitating cell and tissue depots. To this end, ART nanoparticles that target the folic acid (FA) receptor and permit cell-based drug depots were examined using pharmacokinetic and pharmacodynamic (PD) tests. FA receptor-targeted poloxamer 407 nanocrystals, containing ritonavir-boosted atazanavir (ATV/r), significantly increased drug bioavailability and PD by five and 100 times, respectively. Drug particles administered to human peripheral blood lymphocyte reconstituted NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ mice and infected with HIV-1ADA led to ATV/r drug concentrations that paralleled FA receptor beta staining in both the macrophage-rich parafollicular areas of spleen and lymph nodes. Drug levels were higher in these tissues than what could be achieved by either native drug or untargeted nanoART particles. The data also mirrored potent reductions in viral loads, tissue viral RNA and numbers of HIV-1p24+ cells in infected and treated animals. We conclude that FA-P407 coating of ART nanoparticles readily facilitates drug carriage and antiretroviral responses.